Coordination environments of Pt single-atom catalysts from NMR signatures - Jonas Koppe; Alexander V. Yakimov; Domenico Gioffrè; Marc-Eduard Usteri; Thomas Vosegaard; Guido Pintacuda; Anne Lesage; Andrew J. Pell; Sharon Mitchell; Javier Pérez-Ramírez; Christophe Copéret (Nature, 2025)
Abstract Supported metal catalysts that integrate atomically dispersed species with controlled structures lie at the forefront of catalytic materials design, offering exceptional control over reactivity and high metal utilization, approaching the precision of molecular systems 1–3 . However, accurately resolving the local metal coordination environments remains challenging, hindering the advancement of structure–activity relationships needed to optimize their design for diverse applications 1,2 . Although electron microscopy reveals atomic dispersion, conventional spectroscopic methods used in heterogeneous catalysis only provide average structural information. Here we demonstrate that 195 Pt solid-state nuclear magnetic resonance (NMR) spectroscopy is a powerful tool for characterizing atomically dispersed Pt sites on various supports, so called single-atom catalysts (SACs). Monte Carlo simulations allow the conversion of NMR spectra into SAC signatures that describe coordination environments with molecular precision, enabling quantitative assessment of Pt-site distribution and homogeneity. This methodology can track the influence of synthetic parameters, uncovering the impact of specific steps and support types, and can also monitor changes upon reaction. It offers critical insights for the reproducible development of SACs with targeted structures. Beyond SACs, this approach lays the foundation for studying more complex architectures, such as dual-atom or single-cluster catalysts, containing various NMR-active metals.